Production of ‘‘Tomaloo’’ Plant Through Grafting Tomato on Potato at IUBAT: A Promising Technology for Bangladesh Agriculture (IUBAT Review, 2024)
An experiment was conducted at the Agricultural Research Field of International University of Business Agriculture and Technology (IUBAT), Dhaka, Bangladesh from November 2017 to March 2018 to investigate the potentiality of producing tomato and potato from a single plant using grafting technology. In this study, tomato was used as scion and potato as rootstock. Two tomato varieties such as Red Cherry tomato, BARI Tomato-15, and a potato variety Diamant were used in this experiment. Regarding their respective success of grafting on potato, both tomato varieties showed a higher degree of compatibility. The Cherry tomato variety showed 96% success in the union process, while the BARI Tomato-15 showed 94% success. The maximum plant growth was found in Cherry tomato from both non-grafted and grafted plants being 130.56 cm and 115.06 cm respectively. Whereas, 108.36 cm and 95.44 cm were recorded from BARI Tomato-15 non-grafted and grafted plants respectively. The grafted plant (Cherry tomato + Potato) produced 2.73kg tomato + 0.48kg potato per plant and BARI Tomato-15 + Potato produced 2.3kg tomato + 0.49kg potato per plant respectively. Whereas a single Cherry tomato plant produced 3kg of tomato, BARI Tomato-15 produced 2.91kg of tomato and Diamant produced 0.56kg of potato per plant.IUBAT Review—A Multidisciplinary Academic Journal, 7(2): 114-124